The effect of including a calcium soap in the diet and ambient temperature on lactating rabbits - Fernández Carmona J.; Cervera C.; Blas E. (Rabbit production in hot climates, 1994)
Three diets (1, 2, 3) with similar values for fibre and protein, and 28, 68, 106 g EE/kg DM, adding 0, 3, 6 per cent of calcium soap respectively, were used, the values for DE content being 11.1, 11.5, 11.7 KJ/g DM, respectively. 128 litters housed in a climatic chamber at 30 degrees Celsius or in a traditional building, where mean minimum temperatures varied between 9 and 24 degrees Celsius, and fed ad libitum on the experimental diets from 21 to 35 days of age, were controlled. Solid feed intake in suckling rabbits and liveweight at weaning were adversely affected (P less than 0.001) by high temperature.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)